Traducción y adaptación transcultural del cuestionario para niños “Barriers and facilitators of sports in children with physical disabilities (BaFSCH)” para su uso al español en Chile (Transcultural translation and adaptation of the questionnaire for chi - Muñoz Hinrichsen, Fernando Ignacio; Martínez Aros, Alan Frederik; Herrera Miranda, Felipe (Retos, 2022)
El objetivo de este estudio fue realizar una adecuación transcultural del cuestionario “Barriers and facilitators of sports in children with physical disabilities” al idioma español hablado en Chile. Para el proceso de traducción y adaptación transcultural se siguieron los pasos de traducción directa, síntesis de traducciones, traducción inversa, consolidación de comité de expertos y pre-test. En cuanto a los resultados se realizaron los pasos según la metodología desarrollando las adaptaciones necesarias que se consideraron desde la opinión de los expertos y traductores que participaron de la adaptación del escrito. Participaron 93 sujetos con un promedio de edad de 13,95 años ± 4,84 donde hubo 42 niñas (45,16%) y 51 niños (54,84%). La mayoría de las y los participantes asisten a educación básica (62,36%), con condiciones no definidas (34,40%) seguido de quienes tiene dificultades para movilizarse (12,90%) y quienes no comprenden bien las indicaciones (12,90%). Se considera que este cuestionario puede ser una herramienta adecuada para conocer la percepción de los participantes lo que puede finalmente impactar en diversas acciones y políticas que permitan la participación efectiva en actividad física y deporte bajo un enfoque de derecho social.Abstract. The objective of this study was to carry out a cross-cultural adaptation of the questionnaire “Barriers and facilitators of sports in children with physical disabilities” into the Spanish language spoken in Chile. For the translation and cross-cultural adaptation process, the steps of direct translation, translation synthesis, reverse translation, consolidation of the expert committee and pre-test were followed. Regarding the results, the steps were carried out according to the methodology developing the necessary adaptations that were considered from the opinion of the experts and translators who participated in the adaptation of the writing. 93 subjects participated with an average age of 13,95 ± 4,84 years, where there were 42 girls (45,16%) and 51 boys (54,84%). Most of the participants attend basic education (62,36%), with undefined conditions (34,40%) followed by those who have difficulties to move around (12,90%) and those who do not understand the indications well (12,90%). It is considered that this questionnaire can be an adequate tool to know the perception of the participants, which can ultimately impact on various actions and policies that allow effective participation in physical activity and sport under a social law approach.